Disaster Resilient Village Effectiveness Program (Study in Citepus Village, Sukabumi, Indonesia) - Paramita, Cici; Sampurna, Rizki Hegia; Purwanti, Dian (Universitas Muhammadiyah Gorontalo, 2023)
Among the 38 villages in Sukabumi Regency that have implemented the Disaster Resilient Village program, Citepus Village was chosen by BPBD Sukabumi Regency to implement this program because it has a high disaster risk. However, if we look at the level of capacity, Citepus Village is classified as a village with a low level of capacity, this shows that the community and village officials in disaster management are still relatively low or poor. The aim of this research is to find out how the Disaster Resilient Village program is implemented in Citepus Village, Palabuhan Ratu District, Sukabumi Regency. The method used in this research is quantitative with a descriptive approach. The population in this study were Citepus residents, with a sample size of 100 respondents. In this research, researchers used data collection techniques, namely observation, questionnaires/surveys, and literature study. Data analysis and hypothesis testing used in this research are validity testing, reliability testing, hypothesis testing, t test. The findings in this research are the Disaster Resilient Village Program in Citepus Village, Effectiveness, Disaster Resilient Village Program. Effectiveness, defined as the degree of goal achievement, is crucial in gauging organizational progress. In conclusion, community knowledge and awareness are pivotal in mitigating disaster risks and losses. The findings emphasize the efficacy of community-driven disaster resilience initiatives and advocate for proactive, preventive measures in disaster management.